Regulation of microstructure and physical properties of Tb-Dy-Fe-Cu alloys by doping with transition elements - Guolin Xiao (Materials & Design, 2022)
The Tb-Dy-Fe alloy with superior magnetostrictive strain and excellent energy density is applied in various fields such as precise driving and intelligent sensing. However, the Laves phase of magnetostrictive alloys has severe brittleness and poor fracture toughness at room temperature, limiting the development of their engineering instruments. In the present study, the transition element doping method is proposed to regulate the elemental composition for the severe brittleness of Tb-Dy-Fe-Cu alloys. The values of Vickers hardness for Nb-doped and Ti-doped specimens were 520.82 HV and 531.90 HV, respectively, with an increase of 4.097% and 6.311% compared to the original specimens. The saturation magnetostriction coefficient is 800p.p.m. for the natural specimens and around 620p.p.m. for the doped specimens. On the one hand, the enhancement of the mechanical properties of doped specimens is mainly attributed to the growth twins and nanoprecipitates induced by doping the transition element. On the other hand, the weakened magnetic properties of the doped specimens ascribed to the accumulations consisting of nanoprecipitates, twins, and elemental aggregates. This doping method could provide an essential reference for developing novel magnetostrictive materials with more desirable and balance physical properties.